Prevalent Diseases and Mortality in Egg Type Layers: An Overview - Usman, B.A.; Diarra, S.S. (International Journal of Poultry Science, 2008)
Mortality plays a major role in determining profitability of egg type layers, as it is a function of culled and dead birds. Negative association between mortality and net profit has been reported. Higher mortality and culling were reported to be due to severe outbreaks of infectious/non-infectious diseases, accidental deaths, substandard health and management practices and poor quality of chicks and feed. Newcastle (ND), Infectious bursal disease (IBD), yolk sac infections and coccidiosis were found to cause maximum mortality (over 30%) in egg type layers. Infectious laryngotracheitis (IL) caused mortality within the range of 0.81 - 20% in layers. Cannibalism was also reported to be a major cause of death in egg type layers. A drop of 10-40% in egg production was found with the incidence of infectious coryza, E. coli, mycoplasmosis, coccidiosis, egg prolapse and aflatoxicosis. Salmonellae were abundantly found in bedding material of chicken (42%), drinkers (36%), feed (28%) and water tanks (17%) of the poultry farm. Maintenance of a healthy environment in a poultry shed, protection of birds from extreme climatic conditions, maintenance of standard hygiene measures and antibiotic therapy, were reported as key factors in the reduction of losses due to diseases and mortality in egg type layers.